Morphofunctional model characteristics of ice hockey players across different playing positions - Khilchenko, A.D.; Udalova, M.A.; Prokhorenko, A.A.; Kiryanova, L.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and experimentally validate a methodology for improving the technical and tactical skills of the libero in defense during the athletic development phase. Methods and structure of the study. The research was conducted at the P.F. Lesgaft National State University of Physical Culture, Sport, and Health in St. Petersburg. The sample consisted of 46 male volleyball players aged 18 to 25, with qualification levels ranging from 1st class to Master of Sports. Two equal groups were formed – a control group and an experimental group, each consisting of 23 participants. The methodology involved a strict distribution of training load across priority training areas: development of anticipatory abilities (15%), specialized coordination training (20%), and situational simulation of game scenarios (30%). The combination of these training blocks ensured the structured development of skills for applying defensive actions in competitive settings. Results and conclusions. The experiment showed that the level of tactical awareness increased by 18.2%, the effectiveness of receiving an attacking shot increased by 14.7%, while the success rate of receiving a serve increased by 9.3%. Anticipation of the spatiotemporal parameters of the ball’s movement underwent the most pronounced transformation, exceeding the control group’s indicators by 2.8 times and showing a 22.3% increase. The identified patterns confirm the fundamental role of perceptual-cognitive indicators in the initial stages, the accelerated growth of which lays the foundation for improving a volleyball player’s technical and tactical actions.